Cyclopia Extracts Enhance Th1-, Th2-, and Th17-type T Cell Responses and Induce Foxp3+ Cells in Murine Cell Culture - Murakami, Shiho; Miura, Yutaka; Hattori, Makoto; Matsuda, Hiroshi; Malherbe, Christiaan J.; Muller, Christo J. F.; Joubert, Elizabeth; Yoshida, Tadashi (Planta Medica, 2018)
Cyclopia genistoides, one of the traditional South African medicinal plants, and other species of the same genus offer noteworthy phenolic profiles, in particular high levels of the anti-allergic xanthone mangiferin. Hot water and 40% ethanol-water (v/v) extracts, prepared from C. genistoides, Cyclopia subternata, and Cyclopia maculata, were tested for immune-regulating activity in vitro using murine splenocytes and mesenteric lymph node cells. The 40% ethanol-water extracts of C. genistoides and C. subternata significantly enhanced production of several types of cytokines, including IL-4, IL-17, and IFN-γ, by antigen-stimulated splenocytes. A concentration-dependent response was observed, noticeably for IFN-γ production. The activity of the extracts did not correlate with the content of any of the major phenolic compounds, indicative that other extract constituents also play a role in immunomodulation. Additionally, the increased ratio of CD4+CD25+Foxp3+ Treg cells to total CD4+ cells indicated induction of Foxp3+ cells when mesenteric lymph node cells were cultured in the presence of these two extracts. This study is the first reporting immunostimulatory activity for Cyclopia, which are widely consumed as the herbal tea known as honeybush, underpinning further investigations into the potential use of its extracts as adjuvants for mucosal immunotherapy.
Keywords: Cyclopia Vent.; cytokines; Foxp3+; T cell proliferation; Th1; Th2; Th17